2017
DOI: 10.9775/kvfd.2016.17261
|View full text |Cite
|
Sign up to set email alerts
|

Broilerlerden İzole Edilen Termofilik Campylabacter’lerin Genotipik, Antimikrobiyal Direnç ve Virulens Profilleri

Abstract: The objective of this study was to investigate the prevalence, antimicrobial resistance and genetic determinants of resistance of Campylobacter jejuni and Campylobacter coli isolated from commercial broiler farms in Adana and Hatay provinces, Turkey. The assessment of the genetic diversity among the isolates was determined by flaA based RFLP-Polymerase Chain Reaction (PCR) with restriction enzyme DdeI and sequence analysis of short variable regions (SVRs) of flaA and flaB-SVR genes. Antimicrobial susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
4
2
0
Order By: Relevance
“…Higher resistance rate to ciprofloxacin is highly important, because the FQs are drug of choise for the treatment of Campylobacter ASLANTAŞ infections. These findings are almost similar to previous studies in broilers [9] , chicken meat [8] and humans [10] in Turkey.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Higher resistance rate to ciprofloxacin is highly important, because the FQs are drug of choise for the treatment of Campylobacter ASLANTAŞ infections. These findings are almost similar to previous studies in broilers [9] , chicken meat [8] and humans [10] in Turkey.…”
Section: Discussionsupporting
confidence: 92%
“…However, tetO was also detected in four tetracycline-susceptible Campylobacter (two C. jejuni and two C. coli), and the gene was not detected in one tetracycline-resistant C. coli isolate. This finding is not surprising because similar findings have already been reported by some investigators [9,20] . Guévremont et al [41] reported that tetO might be present in tetracycline resistant isolates but might be detected by primers used.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations